A validated LC–MS/MS method for the simultaneous determination of 20‐(S)‐protopanaxatriol and its two active metabolites in rat plasma: Application to a pharmacokinetics study. Issue 23 (27th October 2017) - Qiu, Xin; Yang, Jiali; Wang, Wei; Wu, Qiuhong; Shao, Hong
Abstract: We present a validated liquid chromatography with tandem mass spectrometry method for simultaneous determination of 20‐( S )‐protopanaxatriol and its two oxidative stereoisomeric metabolites (20 S, 24 S )‐epoxy‐dammarane‐3, 6, 12, 25‐tetraol (M1) and (20 S, 24 R )‐epoxy‐dammarane‐3, 6, 12, 25‐tetraol (M2) in rat plasma. 20‐( S )‐Protopanaxatriol, M1, and M2 were extracted with methanol and separated on an ACQUITY HSS T3 column. The mass spectrometry detection was accomplished in selected reaction monitoring mode with precursor‐to‐product ion transitions of m/z 493.4→143.1 for M1 and M2, m/z 475.4→391.3 for 20‐( S )‐protopanaxatriol, and m/z 459.4→375.3 for 20‐( S )‐protopanaxadiol (internal standard). The method showed good linearity over the concentration ranges of 1–1000 ng/mL for 20‐( S )‐protopanaxatriol and 0.5–200 ng/mL for M1 and M2, with correlation coefficients of more than 0.995. The lower limits of quantification for 20‐( S )‐protopanaxatriol, M1, and M2 were 1, 0.5, 0.5 ng/mL, respectively. The intra‐ and interday precisions (RSD, %) were less than 10.41% while the accuracy (relative error, %) ranged from –3.14 to 8.73%. Under the current conditions, M1 and M2 were completely separated within 3 min. The validated assay was successfully applied to evaluating pharmacokinetic profiles of 20‐( S )‐protopanaxatriol, M1, and M2 in rat.